DIAGNOSIS AND CORRELATION OF INDIVIDUAL COGNITIVE DEVELOPMENT AS A FACTOR IN EDUCATIONAL EFFECTIVENESS - Mirzajonova Eleonora Topvoldievna (Bright Mind Publishing, 2025)
The article addresses the issue of cognitive development in preschool-aged children as a result of the interplay between various objective and subjective factors. Particular attention is given to the importance of early diagnosis and targeted support of cognitive functions as essential conditions for ensuring educational effectiveness and the successful personal development of the child.
Keywords: Cognitive development, genetic factors, intelligence, symbolic thinking, psychological stimulation, motor and speech development.